Moho Geometry of the Okinawa Trough Based on Gravity Inversion and Its Implications on the Crustal Nature and Tectonic Evolution - Zhang, Liang; Luan, Xiwu (Frontiers in Earth Science, 2021)
The Okinawa Trough (OT) is an incipient back-arc basin, but its crustal nature is still controversial. Gravity inversion along with sediment and lithospheric mantle density modelling are used to map the regional Moho depth and crustal thickness variations of the OT and its adjacent areas. The gravity inversion result shows that the crustal thicknesses at the northern OT are between 17-22 km, 11-19 km at the central OT, and 7-19 km at the southern OT. Because of the crust with thickness larger than 17 km, the slow southward arc movement and scarce contemporaneous volcanisms, the northern OT should be in the stage of early back-arc extension. All of the moderate crustal thickness, high heat flow and intense volcanism at the central OT indicate that this region is probably in the transitional stage from the back-arc rifting to the oceanic spreading. Only 7-km thick crust, lithosphere strength as low as the mid-ocean ridge and the MORB-similar basalts at the southern OT demonstrate that the southern OT is at the early stage of seafloor spreading.